Efeito antioxidante e gastroprotetor de uma fração polissacarídica sulfatada isolada da alga vermelha Solieria filiformis - Sousa, Willer Malta de (2015)
The red marine algae are considered a rich source of bioactive molecules with numerous pharmacological properties described in the scientific literature. In this study the red marine algaSolieria filiformis was subjected to extraction with papain enzyme to obtain a sulfated polysaccharide (PLS). The extracted material was submitted to spectrophotometric test of chemical composition having high purity with high quantity of sulfation (1,08). Moreover, a chemical structural characterization by Fourier transformer infrared spectroscopy and by nuclear magnetic resonance spectroscopy of 1H proton and 13C carbon was applied, bringing a conclusion where the PLS is classified as a iota-carrageenan. The average molecular weight (210.9 kDa) was verified through Gel Permeation Chromatography (GPC) showing a homogeneous system. Were performed in vitro tests antioxidants (Scavenging of free radical DPPH, chelating ferrous ability and total antioxidant capacity) of fraction PLS in various concentrations (0.025, 0.050, 0.1, 0.5, 1.0, 2.0 and 4.0 mg.mL-1), using as control BHT and EDTA in concentrations of 2.0 and 4.0 mg.mL-1, respectively. The PLS showed an IC50 of 1.77 mg.mL-1 in scavenging of DPPH and total antioxidant capacity an IC50 found was of 2.01 mg.mL-1, while the iron chelator capacity was approximately 39% at a dose of 4mg.mL-1. Futhermore, the protective effect of PLS against ethanol-induced gastric lesions with subsequent dosage of biochemical markers, which include the glutathione (GSH), malondialdehyde (MDA) and hemoglobin (Hb).The gastroprotective effect of PLS with dose dependent manner, with better response at a dose of 10 mg.Kg-1. GSH levels remained high in the treated group with PLS, with significant reduction of MDA concentration, suggesting that the gastroprotective property is partly due to the antioxidant properties by inhibition of free radicals and lipid peroxidation. In addition to reducing the levels of Hb, it suggests a reduction in haemorrhagic lesions caused by ethanol. The results obtained from this research show potential for PLS of seaweed Solieria filiformisbe used in future as a gastroprotective compound due to its antioxidant activity.